Relationship of Parental Role and Self-Conrol Towards Adolescent Premarital Sexual Behaviour - Shafa Amanda Tasya Kamila; Ermiati Ermiati; Raini Diah Susanti (Indonesian Journal of Global Health Research, 2024)
In Indonesia, the rate of premarital sexual behavior among adolescents continues to increase. In fact, HIV/AIDS and unwanted pregnancies cases increases every year as a result of adolescent premarital sexual behavior. The factors that can influence adolescent premarital sexual behavior is parental role in educating, guiding, and accompanying their children and self-control of adolescents. This study aims to determine the relationship between parental role and self-control towards adolescent premarital sexual behaviour in SMA “P” Kota Bandung. The research method used was a quantitative correlation with a population of 556 students from 10th to 11th grade. The sample was taken using purposive sampling technique with a total of 235 respondents were obtained. The research data were obtained using a questionnare regarding parental role, self-control, and premarital sexual behavior. The research data analyzed by using univariate and bivariate analysis with Spearman Rank correlation test. The results showed that a significance value of p = 0,000 (p value < 0,05) was obtained for the parental role and p value of 0,000 (p value < 0,05) for the self-control. It can be concluded that there was significant relationship between parental role and self-control with adolescent premarital sexual behavior in SMA “P” Kota Bandung.